臺灣四套語文教科書的價值取向研究A Study on the Value-Orientation Embedded in the Current Four Sets of Chinese Language Textbooks of Junior Secondary Schools in Taiwan - 何文勝Man-Sing Ho (Higher Education Foundation, 2008)
本文主要是從公民的道德價值來研究臺灣四套現行初中語文教科書的價值取向，以了解這四套初中教科書價值取向的內容、比重和呈現方法。透過研究，我們才能更有效地評估這些教科書有沒有落實課程綱要中教學目標的價值取向。研究首先利用文獻建構教科書價值取向的分析框架，然後採用先定性，後定量的研究方法。 數據顯示，這四套教科書的三個年級都缺了世界層面價值取向的範疇，其他一些年級在家庭、國家、民族或自然等都有不足，可以說，四者都未能發揮「教科書是價值取向的載體」的應有功能。但各項範疇的比重則還有商榷的餘地，例如，四者在個人的量太多，而國家、民族與世界的比重就有不足，這樣課程文件中的教學目標就難全面落實。教科書的價值取向應按學生認知心理發展的方式來呈現才較合理，但不少呈「Λ」或「V」的發展，說明選材量比較隨意。如果課程文件能在不同範疇價值取向的質與量方面皆有一個明確的比重建議，則教科書的編寫才有依據，教科書也才能有質量的保證。 This article examines the value-orientation embedded in the current four sets of Chinese language textbooks of junior secondary schools in Taiwan from the perspective of citizen's moral value. It aims to understand the content, the proportion and ways of presentation of the value-orientation in the textbooks. Through such a research, it is more effective for us to examine whether the value-orientation, which is set as one of the teaching objectives in the curriculum syllabus, has been implemented in the textbooks. This research began with building an analytical framework based on the literature review, and then it employed qualitative research method in first place and quantitative research method in the second place for data analysis. The results of the research showed that the category of value-orientation at the world level was missing in the textbooks throughout all the three forms of the secondary schools, while those at the levels of family, nation, ethnicity and nature were also found missing more or less. In short, the four sets of textbooks failed to play the designated function such as that "textbooks are vectors of value-orientation". However, there is still a room for improvement on the proportion of each category. For example, category at individual level accounted for too much in the four sets of textbooks while categories at national and ethnic levels were far less in the proportion of them. This made it hard to implement the teaching objectives set by the curriculum documents. It is suggested that the value-orientation of the textbooks should be based on the students' psycho-cognitive development. However, the development of a number of "Λ" or "V" indicated that it is on a random basis that the textbook material was selected. Recommendations are made as follows. If there were definite criteria in suggesting the proportion on the quality and quantity of value-orientation in various areas, not only a basis for the textbook compiling could be laid, but also the quality of the textbooks could be assured.